Rape jokes aren't funny: the mainstreaming of rape jokes in contemporary newspaper discourse. Issue 3 (2nd April 2020) - Lockyer, Sharon; Savigny, Heather
ABSTRACT: The #MeToo campaign has reminded us that male sexual violence, harassment, and abuse towards women is not a new phenomenon. But alongside the visibility of the perpetrators and experiences of myriad women, this recent campaign raises a set of questions as to how this type of violence towards women is normalised and legitimated. Our focus here is on the ways in which male sexual violence towards women is normalised and legitimated through the use of humour. Existing research on responses to, and discussions of, rape jokes and rape culture have primarily focussed on online discourses or television coverage of rape joke controversies. The focus in this paper is if, and how, serious newspaper discourse contributes to the normalisation of male sexual violence towards women. In order to evaluate this, we undertake a thematic analysis of UK newspaper coverage of rape jokes. While there is the potential for the telling of rape jokes to be emancipatory, our findings suggest that news coverage of rape jokes does the ideological work of strengthening rather than challenging gendered power relations. We argue that news coverage of rape jokes in the UK predominantly reinforces and normalises male sexual violence towards women.